Comparing Percutaneous to Open Access for Extracorporeal Membrane Oxygenation in Pediatric Respiratory Failure. Issue 10 (October 2018) - Cairo, Sarah B.; Arbuthnot, Mary; Boomer, Laura; Dingeldein, Michael W.; Feliz, Alexander; Gadepalli, Samir; Newton, Christopher R.; Puligandla, Pramod; Ricca, Robert; Rycus, Peter; Vogel, Adam M.; Yu, Guan; et al.
Abstract : Objectives: Evaluate trends in method of access (percutaneous cannulation vs open cannulation) for pediatric extracorporeal membrane oxygenation and determine the effects of cannulation method on morbidity and mortality. Design: Retrospective cohort study. Setting and Subjects: The Extracorporeal Life Support Organization's registry was queried for pediatric patients on extracorporeal membrane oxygenation for respiratory failure from 2007 to 2015. Inverventions: None. Measurements and Main Results: Of 3, 501 patients identified, 77.2% underwent open cannulation, with the frequency of open cannulation decreasing over the study period from approximately 80% to 70% ( p < 0.001). Percutaneous cannulation patients were more commonly male (24.2% vs 21.5%; p = 0.01), older (average 7.6 vs 4.5 yr; p < 0.001), and heavier (average 33.0 vs 20.2 kg; p < 0.001). Subset analysis of patients on venovenous extracorporeal membrane oxygenation revealed higher rates of mechanical complications due to blood clots (28.9% vs 22.6%; p = 0.003) or cannula problems (18.9% vs 12.7%; p < 0.001), cannula site bleeding (25.3% vs 20.2%; p = 0.01) and increased rates of cannula site repair in the open cannulation cohort. Limb related complications were not significantly different on subset analysis for venovenous extracorporeal membrane oxygenation patients stratified by access site. Logistic regression analysis revealed that method of access was not associated with a difference in mortality. Conclusions: The proportion of pediatric patients undergoing percutaneous extracorporeal membrane oxygenation cannulation is increasing. Mechanical and physiologic complications occur with both methods of cannulation, but percutaneous cannulation appears safe in this cohort. Further analysis is needed to evaluate long-term outcomes with this technique. Abstract : Supplemental Digital Content is available in the text.